STUDY OF THE CONCENTRATION OF COPPER, NICKEL AND CADMIUM IN VARIOUS TYPES OF SOILS - Rakhmatov Ulmas; Khamrakulova Muborak Khakimovna; Abdisamatov Elmurodjon Dilmurodovich (Journals Park Publishing, 2022)
The concentrations of copper, nickel and cadmium were studied depending on their time of development in various types of soils in the Andijan region. Metal concentrations were determined by atomic absorption analysis on AAS-3.
Keywords: copper; nickel; cadmium